Unscrewed : Salvage and Reuse Motors, Gears, Switches, and More from Your Old Electronics - Sobey, Ed, ....- (Chicago : Chicago review press, 2011)
Admit it: you love to explore how things work. Screwdriver and pliers in hand, no castoff electronics or old appliances are safe. But once you've pulled apart your prey, do you really just want to screw it back together again . . . assuming you could? Unscrewed is the perfect resource for all UIYers--Undo It Yourselfers--looking to salvage hidden treasures or repurpose old junk. Author Ed Sobey will show you how to safely disassemble more than 50 devices, including: Laser Printer, Radio-Controlled Car, Zip Drive, Videocassette Recorder, Paper Shredder, Audiocassette Player, Electric Drill, Computer Mouse, Keyboard, Fax Machine, Joystick, Floppy Drive, Videocassette Camera, Electric Clock, and More! Each deconstruction project includes a "treasure cache" of the components to be found, a required tools list, and step-by-step instructions, with photos, on how to extract the working components. It also includes suggestions on how to repurpose your electronic finds. Why pay good money to an electronics store when you probably already have what you need in that old VCR, printer, or hair dryer? Fight the mindset of planned obsolescence--there's technological gold in that there junk!
Keywords: Oude electronica; electronica